2018
DOI: 10.5530/ijopp.11.2.16
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Reporting of Adverse Drug Reactions Due to Cardiovascular Drugs in Patients Admitted to a Secondary Care Hospital in Northern Emirate- a Prospective Surveillance Study

Abstract: Context: Adverse drug reactions (ADRs) can result in a number of consequences, ranging from allergic reactions to permanent harm thereby causing morbidity and mortality leading to an increase in the health care costs. Aims: The main objective of the present study was to assess the prevalence of adverse drug reactions due to cardiovascular drugs in patients admitted to a secondary care hospital. Material and Methods: This was a prospective surveillance study which included adult patients of either gender who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
4
5
0
5
Order By: Relevance
“…17 In the present study 165 (94.82%) of ADRs were of mild severity, 9 (5.17%) of ADRs were moderate and none of the ADRs were severe, but study conducted by Tarun Wadhwa et al, it was found that 53% of ADRs were of mild severity, 41 (38%) ADRs were moderate and only 9% of ADRs were severe in nature. 18 In the present study most of the ADRs were managed by reducing the dose followed by symptomatic management. Among 14 patients received spironolactone, 3 patients developed gynaecomastia which required drug withdrawal in 2 of them.…”
Section: Discussionmentioning
confidence: 67%
“…17 In the present study 165 (94.82%) of ADRs were of mild severity, 9 (5.17%) of ADRs were moderate and none of the ADRs were severe, but study conducted by Tarun Wadhwa et al, it was found that 53% of ADRs were of mild severity, 41 (38%) ADRs were moderate and only 9% of ADRs were severe in nature. 18 In the present study most of the ADRs were managed by reducing the dose followed by symptomatic management. Among 14 patients received spironolactone, 3 patients developed gynaecomastia which required drug withdrawal in 2 of them.…”
Section: Discussionmentioning
confidence: 67%
“…Earlier studies have revealed higher incidences (59.54%) of ADRs in patients of >60 years of age than any other age group. 16 The higher number of ADRs in the old age can be due to the altered pharmacokinetics like a decline in renal function and hepatic function.…”
Section: Discussionmentioning
confidence: 99%
“…Bisoprolol was the most common drug implicated in causing ADRs, specifically, bradycardia as an adverse effect. 31 According to a news article published in Khaleej times in April 19, 2017, there is a significant increase in the number of cases of adverse drug reactions in UAE. Ministry of Health and Prevention, UAE noticed increase number of ADR cases varying from 59 in 2013 to 825 in 2016.…”
Section: Cardiovascular Medications and Adverse Drug Eventsmentioning
confidence: 99%